1737 Epidemiological Aspects of Streptococcal Pharyngeal Infections in Pediatric Population. (October 2012) - Iurian, S; Bera, L; Iurian, SI; Mihut, M; Neamtu, ML; Muntean, A
Abstract : Background: During last 5 years, we noticed an increasing incidence of scarlet fever and streptococcal pharyngitis in our county. Aims: To appreciate the positive results rate for beta-hemolytic pyogenic streptococci in throat specimens (group A streptococci- gAs, group C- gCs, group G- gGs); To evaluate ratio of each streptococcal group pharyngeal infection; To establish correlation between streptococcal infections and diseases that justified throat cultures. Methods: Authors designed a retrospective epidemiological study, analyzing microbiology department data during 14 months period. Inclusion criteria: hospitalized and ambulatory care children aged between 2–18 years (scarlet fever diagnosis, pharyngitis diagnosis, healthy children requesting throat exam). Exclusion criteria: children up to 2 years of age. In order to identify streptococci, authors used Columbia agar with 5% sheep blood, Bacitracin inhibition tests, latex agglutination. Data was statistically analyzed using likelihood ratio. Results: Among 6653 throat cultures, 497 isolates (7.47%) were positive. Ratio for each streptococci group was: group A –88.0%, group C –6.2%, group G –5.8%. Seasonal incidence: higher incidence was reported in February and lower incidence in August. Regarding correlation between patient diagnosis and identified streptococci group in throat specimens (p value =0.000): 112 scarlet fever patients (111 gAs, 1 gGs), 264 pharyngitis patients (234 gAs, 13 gCs, 17 gGs), 121 healthy children (93 gAs, 18 gCs, 10 gGs). Last mentioned patients mean pyogenic streptococci carriers (24.34%). Conclusions: Carriers represents the "infection pool" for community children, maintaining persistence of source infection and explaining diminished efficacy of epidemiological measures and infection outbreaks in pediatric population.